Axillary artery compromise in a minimally displaced proximal humerus fracture: a case report - Sukeik, Mohamed (BioMed Central, 2009)
Minimally displaced fractures of the surgical neck of the humerus are rarely associated with axillary artery injury. The innocuous appearance of the x-rays can be misleading and a missed arterial injury in these fractures could potentially lead to disastrous consequences. We report the case of a patient who sustained a minimally displaced fracture of the proximal humerus with vascular compromise requiring immediate investigation and referral to vascular surgeons. Despite spontaneous resolution of the vascular insult, it is important to remember the association of such fractures with vascular injuries in order to diagnose them early and prevent serious complications including amputation.